Measuring Election Quality Through Organizational Governance and Neutrality of Election Management Apparatus in Indonesia - Nandito Putra; Aidinil Zetra; Irawati Irawati (Politeknik Siber Cerdika Internasional, 2026)
Background: Electoral integrity has emerged as a critical concern in contemporary democratic discourse, particularly amid global democratic backsliding. Indonesia's democratic trajectory shows significant decline, with the 2025 V-Dem report placing it in the 'grey zone', no longer meeting minimum standards of electoral democracy. Public trust in electoral processes fundamentally depends on the organizational governance and neutrality of Election Management Bodies (EMBs).Objective: This study examines how organizational governance and bureaucratic neutrality of election management apparatus influence election quality in Indonesia, employing an integrative framework that connects institutional structures with practical implementation challenges.Method: This qualitative literature review analyzed 32 academic sources from Google Scholar and Scopus databases. Thematic analysis was conducted using a reflexive approach, classifying literature based on institutional structure, bureaucratic behavior, and political interference dynamics.Findings and Implications: The study reveals that election bureaucracy faces structural tensions between procedural rigidity and democratic responsiveness. Bureaucratic politicization, institutional erosion, and inadequate sanction mechanisms significantly compromise electoral integrity. Inter-institutional dynamics between KPU, Bawaslu, and DKPP create coordination challenges that affect election quality.Conclusion: Comprehensive institutional reforms are essential, including restoring independent civil service oversight, strengthening sanction mechanisms, harmonizing fragmented regulations, and enhancing professional capacity of EMBs to restore Indonesia's electoral integrity.